Hoyt, Jackson County - Offerman, Mike (Kansas State University, The Chapman Center for Rural Studies, 2011)
Hoyt, Kansas, started out as a small town where farmers took cattle to transport them on the railroads back to eastern markets. Despite all of the terrible events that have plagued Hoyt throughout its history, the town is still a thriving part of the suburban environment in northeast Kansas.
Mike Offerman , “Hoyt, Jackson County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/42.
Keywords: Holton; Hoyt; Jackson County; Rock School; Rock Island Railroad; W.B. McKeage